A Distributed and Parallel Accelerator Design for 3-D Acoustic Imaging on FPGA-Based Systems - Zhao, Dongdong; Mao, Weibo; Chen, Peng; Hu, Yingtian; Liang, Haoran; Dang, Yuanjie; Liang, Ronghua; Guo, Xinxin (IEEE transactions on computer-aided design of integrated circuits and systems, 2024)
3-D imaging sonar is crucial in the exploration of marine resources, and the development of portable device with high-imaging quality and high-real-time performance is the general trend. However, traditional framework methods are limited by the huge amount of computation brought by high-quality imaging, making it difficult to implement in engineering. To address this issue, we develop 3-D real-time sonar system in an algorithm-hardware co-designed way. An ultrawideband distributed and parallel subarray beamforming algorithm (UWB-DPS) is proposed for 3-D acoustic imaging. This is a multistage array time-frequency beamforming method under a distributed parallel computing architecture. Based on this, we propose field-programmable gate array (FPGA)-based accelerator. It divides a large sonar receiving planar array into multiple parallel subarrays, and complete the beamforming in two stages, which can reduce the calculation load and speeds up 3-D imaging. For engineering implementation, we optimized the sparseness of the planar transducer array, with a sparse rate as high as 97.7%. The experimental results show that the calculation amount of the proposed UWB-DPS algorithm is reduced to 1/5.7 of the traditional framework algorithm, the imaging performance is effectively improved, and the FPGA-based accelerator outperforms the CPU software implementation by 935 × .